INFLUENCE OF SCHOOL FEEDING PROGRAM ON THE RETENTION OF LEARNERS IN PUBLIC PRIMARY SCHOOLS IN KENYA; A CASE OF MOMBASA COUNTY - Bekidusa, Asha; Kisimbii, Dr. JohnBosco (Journal of Education and Practice, 2020)
Purpose: The purpose of the study was to establish the influence of school feeding program on the retention of learners in public primary schools. Methodology: This study was conducted through a descriptive survey research design. A descriptive survey is a present oriented methodology used to investigate populations by selecting samples to analyze and discover occurrences. The survey focused on 60 out of the 188 head teachers and teachers who are beneficiaries of school milk program in all the six sub counties in Mombasa i.e. Mvita, Kisauni, Likoni, Nyali, Jomvu and Changamwe.This gives 31.9 % of the total number of participants in this project. To obtain the study sample for descriptive studies 10% of the accessible population is enough. Simple random and purposive sampling procedures were used in this research. Results: School feeding program influences retention of learners in public primary schools with a reliability value of 0.8 which is considered minimal acceptable thus rejecting null hypothesis therefore meaning that school feeding program has a significant effect on retention of learners in pubic primary schools. Unique contribution to theory, practice and policy: School feeding programmes are often designed to enhance academic performance and cognitive development. Improved nutritional status of school-age children leads to better attention and cognition, and thus, better educational outcome. School feeding can improve attentiveness in class by reducing short-term hunger many children come to school on an empty stomach, yet they remain surrounded by the distracting and disturbing facets of the crisis. The study recommends that the ministry of education should review the School feeding Programme and extend it upper primary classes. They should prioritize supply of food to ensure continuous provision and adequate supply of food for pupils.